Про птиц и зверей - Пришвин Михаил Михайлович (Книги - мои друзья, 2013)
Экземпляры: аб. ДБ (15.08.2016) / Инвентарный номер: 2518 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: П 77 / ББК: 84(2Рос=Рус)6